2014
DOI: 10.3390/nu6041442
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Knowledge of UK Coaches

Abstract: Athletes obtain nutritional information from their coaches, yet their competency in this area is lacking. Currently, no research exists in the UK which has a different coach education system to many other countries. Therefore, the aim of this study was to evaluate the sports nutrition knowledge of UK coaching certificate (UKCC) level 2 and 3, hockey and netball qualified coaches. All coaches (n = 163) completed a sports nutrition questionnaire to identify: (a) if they provided nutritional advice; (b) their lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 24 publications
4
28
2
1
Order By: Relevance
“…These results are identical to those of another research group (4,14,19), which found that trainers hit the highest score in the nutrients category compared to the remaining categories.…”
Section: Sub-category Knowledgesupporting
confidence: 89%
See 4 more Smart Citations
“…These results are identical to those of another research group (4,14,19), which found that trainers hit the highest score in the nutrients category compared to the remaining categories.…”
Section: Sub-category Knowledgesupporting
confidence: 89%
“…The total average knowledge score of all trainers in this study was 51.1%, lower than the results reported by previous studies (2,4,5,11,(13)(14)(15), through which the authors concluded that trainers needed supplementary nutrition training. Subsequently, the study's results proved that Lebanese trainers had incompetent knowledge of sports nutrition.…”
Section: Sports Nutrition Knowledgecontrasting
confidence: 88%
See 3 more Smart Citations